The Mediating Role of Job Satisfaction in the Relationship between Organizational Culture and Job Commitment among Employees in the Ministry of Education in the Sultanate of Oman - Al Habsi, Radhiya; Al Dhuhli, Rabia (Technium Social Sciences Journal, 2023)
The current study aimed to determine the relationship between organizational culture and job commitment in the Ministry of Education in the Sultanate of Oman, with job satisfaction as a mediating variable. To achieve the study objectives, a descriptive-analytical approach was adopted, using path analysis through the Amos ver.24 software in the Statistical Package for the Social Sciences (SPSS). This was done to examine the direct and indirect effects of job satisfaction as a mediating variable in the relationship between organizational culture as an independent variable and job commitment as a dependent variable, based on Baron & Kenny's model (1986((. To answer the research questions, the researcher developed a questionnaire as a data collection tool, consisting of three dimensions: organizational culture, including four dimensions; job commitment, including three items; and job satisfaction, including four dimensions. The study sample consisted of 168 employees from the educational directorates in Muscat, North Al Batinah, and Dhofar in the Sultanate of Oman The results of the study indicated a high level of organizational culture, organizational commitment, and job satisfaction among employees in the Ministry of Education in the Sultanate of Oman. However, the study results showed no significant mediating effect of job satisfaction between organizational culture and job commitment. On the other hand, the results indicated a statistically significant effect of organizational culture, with its dimensions (values, expectations, norms, and beliefs), on organizational commitment with its dimensions (affective, continuance, and normative), in the presence of job satisfaction as a mediating variable with its dimensions (relationship satisfaction with colleagues, satisfaction with work procedures, supervision style, and rewards and incentives). The study recommended the importance of applying principles of integrity and credibility in selecting qualified individuals for administrative positions among candidates, achieving the principle of fairness in dealing with employees, and activating the principle of delegation in making some administrative decisions in the educational directorates in the Sultanate of Oman. Additionally, there is a need to review the system of incentives and promotions to achieve a higher level of job satisfaction among employees in those directorates